Strategies to improve students character through monitoring ramadhan activities at SDN 2 Bawu: Pentingnya Meningkatkan Karakter Peserta Didik, kegiatan ramadhan, shalat dhuha, tadarus ,dan laporan buku ramadhan - Cahyasari, Intannia (LPPM Universitas Buana Perjungan Karawang, 2025)
A problem that still often occurs in life is the lack of character of students. The aim of this research is to explain 1). The importance of improving the character of students from an early age, 2). Strategy to improve students’ character through Ramadhan monitoring activities at SDN 2 Bawu. The approach method used by researchers is descriptive qualitative with case studies where the subject is researched thoroughly. This research used a data triangulation method, namely interviews with PAI teachers, school principals and student, then direct observation at SDN 2 Bawu, as well as documentation analysis. The results of this research are: 1). The importance of improving the character of studets from an early age is intended to produce individuals who are of high quality and have the ability to develop their potential. Studies can build and strengthen characters who have good morals and are centered on Islamic teachings as exemplified by Rasulullah SAW, 2). The strategy to improve the character of students throught ramadhan monitoring activities at SDN 2 Bawu, the results can shape the character of each student, namely creating and attitude of responsibility, caring, discipline, always being honest and fair , working hard, never giving up, humble, tolerant, making a person optimistic and always confident